Raman micro‐spectroscopy applied to treatment resistant and sensitive human ovarian cancer cells. Issue 10 (23rd December 2016) - Moradi, Hamid; Ahmad, Abrar; Shepherdson, Dean; Vuong, Nhung H.; Niedbala, Gosia; Eapen, Libni; Vanderhyden, Barbara; Nyiri, Balazs; Murugkar, Sangeeta
Abstract : Despite the many advances intended to enhance the response to treatment, the survival rate of patients with ovarian cancer has only marginally improved in the past few decades. One major cause for this, is the lack of diagnostics for platinum‐resistant disease. The goal of this study was to determine whether Raman micro‐spectroscopy in conjunction with multivariate statistical analysis could discriminate between chemically fixed cisplatin‐resistant (A2780cp) and cisplatin‐sensitive (A2780s) human ovarian carcinoma cells. Raman spectra collected from individual cells were pre‐processed and subsequently analyzed with Principal Component Analysis – Linear Discriminant Analysis (PCA‐LDA). Statistically significant differences ( P < 0.0001) were observed between the Raman spectra of A2780s and A2780cp cells. A diagnostic accuracy of 82% was obtained using the PCA‐LDA classifier model for the discrimination between the A2780s and A2780cp cells. The loading plot analysis suggests that relative increases in proteins and glutathione in the cisplatin‐resistant cells compared to the cisplatin‐sensitive cellsare most likely the major source of discrimination between the two types of cells. These results support the potential application of Raman spectroscopy in the identification of chemo‐resistant tumors prior to treatment. Abstract : Despite the many advances intended to enhance the response to treatment, the survival rate of patients with ovarian cancer has only marginally improved in the past few decades. One major cause for this, is the lack of diagnostics for platinum‐resistant disease. This paper demonstrates the optical spectroscopic discrimination between platinum‐sensitive and platinum‐resistant human ovarian cancer cells for the first time.